PENERAPAN MODEL PEMBELAJARAN INOVATIF TIPE GUIDED TEACHING PADA PELAJARAN BIOLOGI KELAS X DI SMAN 1 BASA AMPEK BALAI TAPAN KABUPATEN PESISIR SELATAN - Putri, Imelda - (STKIP PGRI Sumbar, 2014)
This research is inspired by studentsâ low learning outcome on biology studentsâ in material ecosystem X grade at SMAN 1 Basa Ampek Balai Tapan in Pesisir Selatan district in academic year 2012/2013. One of the alternative ways to improve studentsâ learning outcome in Biology is to implement innovative learning model with type Guided Teaching, it is expected to improve studentsâ Biology learning outcomes. This research aims to know about the improving of learning outcome by implementing Innovative Learning with type Guided Teaching toward Biology course X grade at SMAN 1 Basa Ampek Balai Tapan in Pesisir Selatan district. Type of this research was Experimental research and research design was Randomized Control Group Posttest Only Design. Technique of data collection was Purposive Sampling. The result of this research can be seen that Experimental class had average score higher than control class. So, it can be conclude that implementing of Innovative Learning Model Guided Teaching type able to improve studentâ learning Biology X grade at SMAN 1 Basa Ampak Balai Tapan in Pesisir Selatan District.